Investigation of the influences on bank selection decisions of well-educated Singaporeans. - Chua, Guan Wee. (2008)
The main objective of this study was to develop a bank selection model using a sampling frame of local undergraduates and working graduates. Further investigations were made to establish if it was important for a bank to offer certain products when the bank selection process was taking place. An exploratory approach was used to see if the Rokeach Value Survey could be used as predictors of bank selection dimensions.